Ensinar - incentivar - mediar: dilemas nas formas de sentir, pensar e agir dos educadores dos CEFFAS sobre os processos de ensino/aprendizagem - Roberto Telau (2015)
In this research, we study the social representation of the CEFFAs' educators about the teaching/learning processes. Given my peasant trajectory of field side educator and studies performed in the RACEFFAES and FAE/UFMG, I realized that there are tensions in how the educators experience these processes: they perceive themselves in the psycho-pedagogic humanistic conception that was historically assimilated by the CEFFAs and are they tensioned to adopt a more critical conception to collaborate with the processes of social transformation demanded by the movement of field side education. We investigate how the educators elaborate their social representations about learning and teaching with distinct theoretical orientation. To understand the question and outline the hypothesis, we build the contextual reference of the CEFFAs about the birth, pedagogical systematization, expansion for Brazil and articulation with field side education. We retrieved studies about learning/teaching in the emphasis in teaching, in the learning and in teaching/learning. We use the epistemological reference of Marx and Gramsci to guide the reading about the object and justify that we want to understand the social representations of the subjects and to participate in the transformation processes demanded by the movements we attend. We are based on the Theory of Social Representations (MOSCOVICI, 2012) when we analyse subjects that experience situations where they need to make decisions, handle conflicts, dealing with consolidated knowledge and re-elaborate them. We used structured quizzes to outline the profile of the educators and narrative interviews to dispose of the processes of formation of social representations. We model the social representation of the educators in three positions: in the first one are the educators that resist to change their social representations and keep the knowledge historically consolidated and do not change the representation; in the second the educators challenge and unbalance themselves but do not re-elaborate their representations. The last are those that can accommodate the new knowledge, re-elaborating the previous one. We concluded that these positions have dynamic form and constitution. We have educators that resist to changes based on the emphasis in the teaching and on the emphasis on the learning. The ones that unbalanced the knowledge, make this from the emphasis from the teaching to the learning, from the teaching to the teaching/learning and from the learning to the teaching/learning. The only ones that re-elaborate, make this in the emphasis in the teaching/learning. We conclude bringing some thoughts: not all educators are oriented by the hegemonic and historical approaches of the CEFFAs; to make CEFFAs collaborate in the social transformation, it is necessary to advance to a theoretical-epistemological critical basis; this research help CEFFAs to advance in this sense and open new fields of research about the processes of elaboration of these representations that explain the causes of the current representations and help to formulate consistent actions to reach the objectives.